IMPLEMENTASI METODE SOROGAN DALAM MENINGKATKAN PEMAHAMAN SANTRI TERHADAP KITAB KUNING: PERSPEKTIF TEORI SOSIOKULTURAL VYGOTSKY - Anisa Khoirun Nikmah; Jaenullah Jaenullah; Rina Mida Hayati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning classical Islamic texts at Tri Bhakti Attaqwa Islamic Boarding School still faces various challenges, particularly in students’ ability to read unvowelled Arabic texts and understand the content independently. Differences in students’ basic abilities also become obstacles in the learning process. This study aims to analyze the implementation of the sorogan method in improving students’ understanding of classical Islamic texts from the perspective of Lev S. Vygotsky’s sociocultural theory. This research employed a qualitative approach with a case study design. The research subjects consisted of female teachers and students participating in sorogan learning activities. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing using triangulation techniques to ensure data validity. The findings indicate that the sorogan method effectively improves students’ ability to read, translate, and understand classical Islamic texts gradually. The learning process reflects the concepts of zone of proximal development (ZPD) and scaffolding, where students develop through direct and gradual guidance from teachers. In addition to improving cognitive abilities, the sorogan method also fosters students’ independence, discipline, and responsibility in learning. Therefore, the sorogan method remains relevant as an effective learning approach for classical Islamic texts in line with modern developmental learning theory. ABSTRAK Pembelajaran kitab kuning di Pondok Pesantren Tri Bhakti Attaqwa masih menghadapi berbagai tantangan, terutama dalam kemampuan santri membaca teks Arab tanpa harakat dan memahami isi kitab secara mandiri. Perbedaan kemampuan dasar antar santri juga menjadi kendala dalam proses pembelajaran. Penelitian ini bertujuan untuk menganalisis implementasi metode sorogan dalam meningkatkan pemahaman santri terhadap kitab kuning berdasarkan perspektif teori sosiokultural Lev S. Vygotsky. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian terdiri atas ustadzah dan santri yang mengikuti kegiatan sorogan. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan teknik triangulasi untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa metode sorogan efektif dalam meningkatkan kemampuan santri membaca, menerjemahkan, dan memahami isi kitab kuning secara bertahap. Proses pembelajaran mencerminkan konsep zone of proximal development (ZPD) dan scaffolding, di mana santri berkembang melalui bimbingan langsung dan bertahap dari ustadzah. Selain meningkatkan kemampuan kognitif, metode sorogan juga membentuk kemandirian, disiplin, dan tanggung jawab santri dalam belajar. Dengan demikian, metode sorogan tetap relevan sebagai metode pembelajaran kitab kuning yang sesuai dengan perspektif teori perkembangan modern.